2010
DOI: 10.2353/ajpath.2010.100199
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Regulation of Reticulon 4B (Nogo-B) in Renal Tubular Epithelial Cells

Abstract: Nogo-B is a member of the reticulon family of proteins that has been implicated in diverse forms of vascular injury. Although Nogo-B is expressed in renal tissues, its localization and function in the kidney have not been examined. Here, we report that Nogo-B is expressed specifically in the epithelial cells of the distal nephron segments in the murine kidney. After unilateral ureteral obstruction (UUO) and ischemia/reperfusion, Nogo-B gene and protein levels increased dramatically in the kidney. This increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…Marin et al have demonstrated a dramatic delay in the recruitment of macrophages in Nogo-B-disrupted mice in vivo , consistent with the findings of Schanda et al that Nogo-B deficiency is associated with reduced promotion of macrophage homing and functional recovery [17, 19]. Thus, it has been suggested that endogenous Nogo-B may be implicated in the control of macrophage activities and trafficking [20].…”
Section: Introductionsupporting
confidence: 61%
“…Marin et al have demonstrated a dramatic delay in the recruitment of macrophages in Nogo-B-disrupted mice in vivo , consistent with the findings of Schanda et al that Nogo-B deficiency is associated with reduced promotion of macrophage homing and functional recovery [17, 19]. Thus, it has been suggested that endogenous Nogo-B may be implicated in the control of macrophage activities and trafficking [20].…”
Section: Introductionsupporting
confidence: 61%
“…(Marin et al. ) reported that Nogo‐B mRNA and protein were dramatically upregulated in renal proximal tubule epithelial cells following unilateral ureteral obstruction. We found a similar large increase in Nogo‐B mRNA in the kidneys of mice treated with Urografin (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…RNA isolation, reverse transcription, and quantitative PCR was performed as described 26 , except that GAPDH was used for normalization of transcript abundance. …”
Section: Methodsmentioning
confidence: 99%